218 Coronary artery disease in athletes: a case report. (8th December 2021) - Colangelo, Lidia; Colangelo, Maria; Gareri, Clarice
Abstract: Aims: Despite the proven benefits of regular physical exercise, and although sportsmen are the paradigm of healthy individuals, the athletes population is not risk-free and can suffer severe clinical conditions including coronary artery disease (CAD) and sudden cardiac death (SCD). Identification of athletes with higher cardiovascular risk is a crucial goal of pre-participation screening. Methods and results: In this report, we discuss the case of a 79-year-old male. He was a cyclist, who performed a visit to the sports doctor to have issued a certificate for competitive fitness. He was dyslipidaemic, hypertensive, diabetic, and he reported no symptoms. The patient's ECG revealed an advanced second-degree atrioventricular block. For this reason, he was admitted to the emergency department and he underwent urgent coronary angiography and a temporary Pacemaker. Indeed, a diagnosis of bivasal coronary artery disease was made, and for the first time the patient was subjected to angioplasty of the anterior descending branch and circumflex branch. Subsequently, for the persistence of bradyarrhythmia, he was subjected to a definitive Pacemaker implant. Conclusions: The benefits of exercise in the overall population are multiple and indisputable, but in athletes with cardiovascular disease exercise can also be associated with adverse clinical events, including SCD. In veterans, a growing group of athletes, CAD is the most common cause of SCD. Detection of subclinical CAD should be the main objective of veteran athlete screening, since the performance of classical cardiovascular risk stratification based on clinical factors appears to be suboptimal.